Pengaruh Tax Planning dan Profitabilitas Terhadap Manajemen Laba Dengan Ukuran Perusahaan Sebagai Variabel Moderating Pada Perusahaan Terdaftar di Bursa Efek Indonesia Periode 2013-2018 - Nurianti Sihombing; Enggar Diah PA; Muhammad Gowon (Magister Ilmu Akuntansi Universitas Jambi, 2020)
This study aims to analyze the effect of tax planning and profitability on earnings management with company size as a moderating variable. The population of this study is companies listed on the Indonesia Stock Exchange (IDX) for the period 2013-2018. The selection of this sample uses a purposive sampling method. Hypothesis testing uses multiple linear regression analysis and Moderated Regression Analysis (MRA) with statistical procedures using SPSS software version 24. The results showed partially that tax planning has an effect on earnings management. Meanwhile, profitability has no effect on earnings management. Simultaneously, tax planning and profitability have effect on earnings management. Based on the results of the MRA interaction test, company size can moderate the effect of tax planning on earnings management, but cannot moderate the effect of profitability on earnings management. Keyword: Tax Planning, Profitability, Company Size, Management Earning.